Pengembangan Permainan NGABU (Ngawi Budaya) Berbasis Kearifan Lokal Jawa Terhadap Nilai Karakter Kesabaran pada Anak Usia 4-5 Tahun - Nurchayati Nurchayati; Narendradewi Kusumastuti; Nur Cahyati Ngaisah (Pusdikra Publishing, 2026)
The low level of patience character among children aged 4–5 years at Dharma Wanita Pucangan Kindergarten is reflected in their inability to wait for their turn, their tendency to become easily frustrated, and their difficulty in remaining calm during simple activities. This study aimed to develop the NGABU (Ngawi Budaya) game based on Javanese local wisdom as a learning medium to foster patience character in early childhood. This study employed the Research and Development (R&D) method using the ADDIE development model. The participants were 20 children aged 4-5 years at Dharma Wanita Pucangan Kindergarten. Data were collected through observation and questionnaires using validation sheets from material experts, media experts, and teachers. Data were analyzed using descriptive quantitative and qualitative techniques, followed by validity and reliability tests. The results showed that the NGABU game obtained an average feasibility score of 92.63%, consisting of material expert validation (93.33%), media expert validation (85.00%), small-group trials (93.33%), and field trials (96.67%), indicating that the product was highly feasible. The reliability test produced a Cronbach's Alpha coefficient above 0.70. In conclusion, the NGABU game is a feasible, attractive, and reliable learning medium for fostering patience character in early childhood. This study contributes an innovative local wisdom-based educational game that supports character education in kindergarten.